Asking the Right Questions : Johannesburg Completes a Groundbreaking Municipal Bond Issue - Ngobeni, Jason (World Bank, Washington, DC, 2012)
In 2004 the city of Johannesburg sold two municipal bond issues, among the very few such issues in Africa. The bond issues marked the city's recovery from near bankruptcy in the mid-1990s. They have been followed by several more as well as an even more ambitious capital financing program. Preparing for a first-time bond issuance is complicated and time consuming. Johannesburg navigated its way with remarkable success by asking the right questions and insisting on credible answers. Its path offers guidance and insights to other local governments considering the use of municipal bonds to finance infrastructure.